2006
DOI: 10.1038/sj.bmt.1705287
|View full text |Cite
|
Sign up to set email alerts
|

Financial burden of national health insurance for treating patients with transfusion-dependent thalassemia in Taiwan

Abstract: The thalassemias are a heterogeneous group of inherited hypochromic anemias of varying severity. The mainstay of supportive treatment is regular blood transfusion accompanied by iron-chelating therapy. Hematopoietic stem cell transplantation (HSCT) provides an alternative option when curative therapy is considered. More than 400 patients in Taiwan have b-thalassemia major or other transfusion-dependent thalassemias, and their treatment costs account for a considerable percentage of the National Health Insuranc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 17 publications
1
28
1
Order By: Relevance
“…The cost of BMT is equivalent to that of a few years of noncurative supportive care. 3,11,12 The standard combination of busulfan and cyclophosphamide (BuCy) is associated with rejection rates ranging from 12% to 35%, 13,14 which prompted the addition of other engraftment-enhancing agents such as thiotepa (Tt) 15,16 or anti-thymocyte globulin (ATG) 13,[17][18][19] to busulfan-or treosulfan-containing regimens. Very long-term follow-up studies have shown that BuCy may be associated with normalization of HRQoL, no second malignancies in the absence of chronic graft-versus-host disease (cGVHD), and preservation of fertility in a significant number of patients transplanted prior to age 15 years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cost of BMT is equivalent to that of a few years of noncurative supportive care. 3,11,12 The standard combination of busulfan and cyclophosphamide (BuCy) is associated with rejection rates ranging from 12% to 35%, 13,14 which prompted the addition of other engraftment-enhancing agents such as thiotepa (Tt) 15,16 or anti-thymocyte globulin (ATG) 13,[17][18][19] to busulfan-or treosulfan-containing regimens. Very long-term follow-up studies have shown that BuCy may be associated with normalization of HRQoL, no second malignancies in the absence of chronic graft-versus-host disease (cGVHD), and preservation of fertility in a significant number of patients transplanted prior to age 15 years.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] In spite of improved iron chelation therapy and safer transfusions, 5 ST remains a severe disease, particularly in developing countries, where often state-of-the-art care is not affordable and/or accessible. ST is also a major indication for blood and marrow transplantation (BMT) in children in the Indian subcontinent.…”
Section: Introductionmentioning
confidence: 99%
“…One advantage of this study is that we used a populational health insurance claims database which covers all age groups among cancer patients. The coverage of age groups of this study is wider than published studies [9,10,16] which cover adults only. One limitation of our study is that we can not investigate the relationship between the severity of cancer and medical costs, and the dose-response relationship between the chemotherapy regimens and the severity of anemia.…”
Section: Discussionmentioning
confidence: 83%
“…13,14 To our knowledge, this study is the first to suggest that the utilization of double-unit UCBT has shown promising results in teenagers with transfusion-dependent thalassemia, although the clinical effectiveness of HSCT over traditional transfusion and chelation therapy has been reported previously. 15 Notably, tolerability and safety were also acceptable in the therapeutically challenging clinical setting of our study. Phlebotomy was not routinely performed in our study, as it may stimulate the hyperplastic bone marrow after HSCT, and the residual recipient cells may also be stimulated.…”
Section: Discussionmentioning
confidence: 83%